2013
DOI: 10.1016/j.cherd.2012.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical investigation on mixing and axial dispersion in Taylor–Couette flow patterns

Abstract: OATAO is an open access repository that collects the work of Toulouse researchers and makes it freely available over the web where possible. This is an author-deposited version published in : http://oatao.univ-toulouse.fr/ Eprints ID : 9828

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 15 publications
(26 reference statements)
1
29
0
Order By: Relevance
“…Previous studies Rudman (1998), Nemri et al (2012) showed that the property of non-uniqueness of TaylorCouette flow could significantly influence axial dispersion. In our previous work Nemri et al (2012), we showed that we can reach a factor 2, in terms of dispersion coefficient, for the same Reynolds number and various wave states. Rudman (1998) had also reported a factor 1.4.…”
Section: Effect Of the Wave Statementioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies Rudman (1998), Nemri et al (2012) showed that the property of non-uniqueness of TaylorCouette flow could significantly influence axial dispersion. In our previous work Nemri et al (2012), we showed that we can reach a factor 2, in terms of dispersion coefficient, for the same Reynolds number and various wave states. Rudman (1998) had also reported a factor 1.4.…”
Section: Effect Of the Wave Statementioning
confidence: 99%
“…We intended to quantify the respective role of intravortex and intervortex mixing on axial dispersion in both TVF and WVF regimes. The influence of the flow bifurcations as well as the multiplicity of wave states is also studied in order to understand the non-monotonic behavior of the axial dispersion coefficient observed in our previous study (Nemri et al 2012). …”
Section: List Of Symbols Subscriptsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a spectral analysis of the data was performed to determine the wave state (axial and azimuthal wave numbers) [28].…”
Section: Taylor-couette Apparatusmentioning
confidence: 99%
“…Intra-vortex transport is then governed by a local coefficient K c and the inter-vortex exchange by a trans- In the present study, we investigate axial dispersion in Taylor-Couette flow patterns from both local and macroscopic points of view. We focus on the mixing mechanisms controlling the axial dispersion in wavy regimes since either numerical [16,28] or experimental [28] …”
Section: Mixing In Taylor-couette Flow: State Of the Artmentioning
confidence: 99%